Potential Applications of Natural Components of Traditional Chinese Medicine Delivery via Nanoparticle Drug Delivery Systems in the Treatment of Alzheimer’s Disease - Lai G; Wu H; Yang K; Hu K; Zhao W; Chen X; Li J; Wang H; Lv Z; Xie G; Wu X (International Journal of Nanomedicine)
Guogang Lai,1,* Hao Wu,2,* Kaixia Yang,1 Kaikai Hu,1 Wen Zhao,1 Xiao Chen,1 Jiayi Li,1 Haifeng Wang,1 Zhongyue Lv,1 Guomin Xie,1 Xiping Wu1 1Department of Neurology, The Affiliated Lihuili Hospital of Ningbo University, Ningbo, Zhejiang, People’s Republic of China; 2Ningbo Institute of Innovation for Combined Medicine and Engineering, The Affiliated Lihuili Hospital of Ningbo University, Ningbo, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiping Wu; Guomin Xie, Department of Neurology, The Affiliated Lihuili Hospital of Ningbo University, Ningbo, Zhejiang, People’s Republic of China, Tel +86 13989315307 ; +86 13957881339, Email wxpdoudou@163.com; drxie01@qq.comAbstract: Alzheimer’s disease (AD), a primary neurodegenerative disorder, is characterized by amyloid-β plaques and tau hyperphosphorylation-induced neurofibrillary tangles. Current treatments only alleviate symptoms, and Aβ monoclonal antibodies raise safety concerns in clinical use. Natural components (NCs) of Traditional Chinese Medicine (TCM) (eg, curcumin, quercetin, berberine, resveratrol) exhibit multi-target neuroprotective effects in AD, but poor blood-brain barrier (BBB) penetration and low bioavailability limit clinical use. Recent strategies to enhance TCM delivery include NP-based nanoparticle (NP) drug delivery systems (NDDS), structural modifications, and combination therapies. NDDS demonstrate superior performance in enabling brain-targeting delivery via passive (paracellular/transcellular) and active (adsorption-/receptor-/carrier-mediated transcytosis) approaches, improving NCs’ stability, controlled release, and bioavailability. With NCs of TCM delivery via NDDS, it is possible to develop intelligent therapeutic systems that combine multi-target regulation with precise drug delivery. This review summarizes the diverse neuroprotective effects of NCs of TCM in AD treatment and discusses the commonly used types of NPs for AD therapy. It particularly focuses on these NCs of TCM delivery via NDDS, covering aspects such as NPs types, fabrication techniques, characteristics, administration routes, and advantages. Finally, the challenges and potential solutions for NCs of TCM were examined, along with comparative advantages and limitations among different NPs and future research directions. Collectively, NCs of TCM delivery via NDDS demonstrate promising therapeutic potential for AD treatment. Keywords: Alzheimer’s disease, Traditional Chinese Medicine, natural components, nanoparticle drug delivery systems